2014
DOI: 10.1111/febs.13096
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for the binding of the membrane‐proximal C‐terminal region of chemokine receptor CCR2 with the cytosolic regulator FROUNT

Abstract: C region to a cytosolic regulator has not been structurally analyzed. The chemokine receptor CCR2 is a member of the GPCR superfamily, and the Pro-C region of CCR2 binds to the cytosolic regulator FROUNT. Studying the interaction between CCR2 Pro-C and FROUNT at an atomic level provides a basis for understanding the signal transduction mechanism via GPCRs. NOE-based NMR experiments showed that, when bound to FROUNT, CCR2 Pro-C adopted a helical conformation, as well as when embedded in dodecylphosphocholine mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…However, these findings have not yet been translated into effective clinical therapies, possibly due to species-specific differences in chemokine receptors or due to redundancy in chemokine signaling. FROUNT promotes chemotactic signaling via CCR2 and CCR5 by binding to a conserved intracellular region of these receptors 14,15,25,40 . Since FROUNT is a molecule involved in signal amplification, its inhibition is expected to have effects different from that of the inhibition of chemokine or chemokine-receptor blockade, as evidenced by the minimal effect on steady-state monocyte population in Frount-deficient mice ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, these findings have not yet been translated into effective clinical therapies, possibly due to species-specific differences in chemokine receptors or due to redundancy in chemokine signaling. FROUNT promotes chemotactic signaling via CCR2 and CCR5 by binding to a conserved intracellular region of these receptors 14,15,25,40 . Since FROUNT is a molecule involved in signal amplification, its inhibition is expected to have effects different from that of the inhibition of chemokine or chemokine-receptor blockade, as evidenced by the minimal effect on steady-state monocyte population in Frount-deficient mice ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…FROUNT interacts with the membrane‐proximal C‐terminal regions of chemokine receptors, CCR2 and CCR5, through FNT‐C (Terashima et al., ; Toda et al., ). The intracellular interaction promotes leukocyte migration, and thus, FROUNT represents a promising target for drug development (Esaki et al., , ; Terashima et al., ; Toda et al., , ).…”
Section: Introductionmentioning
confidence: 99%
“…We have been studying the cytoplasmic protein FROUNT (UniProtKB Q9BW27), a 656-amino acid protein that binds to the membrane-proximal C-terminal intracellular region (Pro-C) of the chemokine receptor CCR2 via its C-terminal 493–656 region, as revealed by yeast two-hybrid assays . FROUNT also binds to Pro-C of CCR5, thereby participating in CCR5-related cell migration .…”
mentioning
confidence: 99%
“…In our structural and functional studies of the interactions between FROUNT and chemokine receptors, we identified a 16-amino acid region of CCR2 Pro-C as the minimal segment responsible for binding to FROUNT . CCR2 Pro-C adopted an amphiphilic helical conformation upon binding to FROUNT and a typical amphiphilic α-helix upon binding to the membrane . The binding sites of FROUNT and the membrane overlap on the same side of the CCR2 Pro-C structure, and Pro-C dynamically switches between the two binding partners.…”
mentioning
confidence: 99%
See 1 more Smart Citation